Analisis Pertumbuhan Ekonomi Indonesia - Ahmad Soleh (Journal Development, 2016)
The high economic growth and continuous in the long run is a target to be achieved by every country in the world, especially developing countries, without exception of the Indonesian state. In achieving these efforts can be done through various approaches and theory development. research entitled "Analysis of Indonesian Economic Growth (Growth Model Endogenius)" aims to: (1) analyze the development of the economy and labor conditions in Indonesia; (2) analyze the conditions which the Indonesian economy. This research uses descriptive quantitative methods and analysis inverensial, using secondary data in the form of time series. The results showed that the independent variables analyzed, the variables that significantly affect output (GDP) is a variable capital (K), while the labor force (L) both total and individual workers for education under diploma (non-graduate) and power work with minimal education diploma (bachelor) had no significant effect on GDP at current prices and at constant prices, except for labor scholar at constant prices had a positive effect but not significant. Furthermore, based on the 4 (four) models tested show that the sum of all the regression coefficient is smaller than 1 each at 0.7292 and 0.3527 on the basis of current prices, as well as for on the basis of constant prices is the sum of all the regression coefficients respectively by 0 , 1078 and 0.2002. Thus showing the scale of the rate of return is declining (decreasing return to scale). It concluded that the current state of Indonesia will enter or toward Era Long Run Economic Growth.